Liminal spaces and identities in Elizabeth Bishop`s poetry - Weiss, Michaela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses the representation and understanding of liminal spaces and identities in the poems "Santarem", "Questions of Travel", "North Haven", and "Crusoe in England" by Elizabeth Bishop (1911?1979), focusing predominantly on her strategies of creating poetic landscapes that are not only geographical but more importantly, psychological, and spiritual.
Keywords: liminality; liminal landscape; Bishop, Elizabeth (1911-1979); Emerson, Ralph Waldo (1803-1882); fluidity; transition